Humoral First-Line Mucosal Innate Defence in vivo - Carl Persson (Karger Publishers, 2020)
Based on observations in vivo in guinea-pig and human airways, this review presents plasma exudation as non-sieved transmission of bulk plasma across an unperturbed mucosa that maintains its normal barrier functions. Several steps have led to the present understanding of plasma exudation as a non-injurious response to mucosal challenges. The implication of a swift appearance of all circulating multipotent protein systems (also including antimicrobial peptides that now are viewed as being exclusively produced by local cells) on challenged, but intact, mucosal surfaces cannot be trivial. Yet, involvement of early plasma exudation responses in innate mucosal immunology has dwelled below the radar. Admittedly, exploration of physiological plasma exudation mechanisms requires in vivo approaches beyond mouse studies. Plasma exudation also lacks the specificity that is a hallmark of biological revelations. These aspects separate plasma exudation from mainstream progress in immunology. The whole idea, presented here, thus competes with strong paradigms currently entertained in the accepted research front. The present focus on humoral innate immunity in vivo further deviates from most discussions, which concern cell-mediated innate defence. Indeed, plasma exudation has emerged as sole in vivo source of major mucosal defence proteins that now are viewed as local cell produce. In conclusion, this review highlights opportunities for complex actions and interactions provided by non-sieved plasma proteins/peptides on the surface of intact mucosal barriers in vivo.